Effect of Eco-Enzyme Dosage Variations in an Intermittent MBBR System on the Efficiency of Domestic Wastewater Treatment: Pengaruh Variasi Penambahan Eco-Enzyme pada Sistem Intermittent MBBR terhadap Efisiensi Pengolahan Limbah Domestik - Adinda Permata Salsabila; Praditya Sigit Ardisty Sitogasa (Media Ilmiah Teknik Lingkungan (MITL), 2026)
This study aimed to analyze the effect of a Moving Bed Biofilm Reactor (MBBR) operated under oxic–anoxic conditions with the addition of an external carbon source in the form of eco-enzyme during the anoxic phase on the reduction of COD and BOD concentrations in domestic wastewater. The investigated variables included oxic–anoxic duration ratios (2:1, 4:1, and 6:1) within an 8-hour operational cycle and eco-enzyme dosages (0%, 0.5%, 1%, 1.5%, and 2%). The results showed that at an oxic–anoxic ratio of 6:1, the addition of 1.5% eco-enzyme achieved COD removal efficiency of up to 87%, while a 2% dosage resulted in BOD removal efficiency of 89%. These findings indicate that the appropriate eco-enzyme dosage enhances the biodegradation of organic compounds and supports biological organic removal in the intermittent MBBR system by creating optimal reactor environmental conditions.